Technicolored Reflections on Race in the Time of TV - duCille, Ann (Duke University Press, 2018)
From early sitcoms such as I Love Lucy to contemporary prime-time dramas like Scandal and How to Get Away with Murder, African Americans on television have too often been asked to portray tired stereotypes of blacks as villains, vixens, victims, and disposable minorities. In Technicolored black feminist critic Ann duCille combines cultural critique with personal reflections on growing up with the new medium of TV to examine how televisual representations of African Americans have changed over the last sixty years. Whether explaining how watching Shirley Temple led her to question her own self-worth or how televisual representation functions as a form of racial profiling, duCille traces the real-life social and political repercussions of the portrayal and presence of African Americans on television. Neither a conventional memoir nor a traditional media study, Technicolored offers one lifelong television watcher's careful, personal, and timely analysis of how television continues to shape notions of race in the American imagination.